2015
DOI: 10.1002/stem.1917
|View full text |Cite|
|
Sign up to set email alerts
|

HPGCD Outperforms HPBCD as a Potential Treatment for Niemann-Pick Disease Type C During Disease Modeling with iPS Cells

Abstract: Niemann-Pick disease type C (NPC) is a lysosomal storage disease characterized by abnormal accumulation of free cholesterol and glycolipids. Here, we established induced pluripotent stem cell (iPSC) lines from NPC patients. Hepatocyte-like cells (HLCs) and neural progenitors derived from the iPSC lines accumulated cholesterol and displayed impaired autophagy and ATP production. A molecular signature related to lipid metabolism was also impaired in the NPC-iPSCderived HLCs. These findings indicate that iPSC-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 47 publications
9
92
2
Order By: Relevance
“…In a recent publication, 2-hydroxypropyl-gamma-cyclodextrin was found to more efficiently reduce the cholesterol accumulation and restore the functional abnormalities in induced pluripotent stem cell lines from NPC1 patients [29]. Preclinical studies have not yet been reported on this compound.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, 2-hydroxypropyl-gamma-cyclodextrin was found to more efficiently reduce the cholesterol accumulation and restore the functional abnormalities in induced pluripotent stem cell lines from NPC1 patients [29]. Preclinical studies have not yet been reported on this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various bioactivities of CyDs have been demonstrated, and CyDs have been used as active pharmaceutical ingredients (APIs) against Niemann-Pick disease type C (NPC), [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] leukemia, 77) hyperlipidemia, 78) Alzheimer's disease, [79][80][81][82][83][84] cerebral ischemic injury, 85) atherosclerosis, 86) diabetic kidney disease, 87) chronic renal failure, 88) AIDS, 89,90) influenza, 91) peripheral artery disease, 92) sterility, [93][94][95] solid cancers, [96][97][98][99][100][101] bacterial growth, 102) α-synucleinopathy, 103) GM1-gangliosidosis, 104) septic shock, [105][106][107] hypervitaminosis, 108) and transthyretin-related familial amyloidotic polyneuropathy (FAP) …”
Section: Cyclodextrin-based Supramolecular Pharmacology and Drug Discmentioning
confidence: 99%
“…Based on the results regarding cholesterol solubilizing potential, attenuating the effects against NPC abnormalities and cytotoxicity induction, HB-β-CyD may be superior in terms of safety and efficacy in Npc1 null cells compared with HE-β-CyD and HB-β-CyD. On the other hand, Soga et al 56) reported that 2-hydroxypropyl-γ-CyD (HP-γ-CyD) could reduce cholesterol accumulation and restore functional and molecular abnormalities in NPC patient-derived cells, more effectively than HP-β-CyD treatment. In addition, NPC model mice showed improved liver status and prolonged survival with HP-γ-CyD.…”
Section: Hp-β-cyd For Treatment Of Niemann-pick Disease Type C (Npc)mentioning
confidence: 99%